Pengaruh Suhu Dan Intensitas Cahaya Terhadap Pertumbuhan Jamur Tiram Di Tangerang - Fenny Amelia; Jose Ferdinand; Klerenita Maria; Michel Geren Waluyan; Indah Juwita Sari (Biogenesis: Jurnal Ilmiah Biologi, 2017)
Oyster mushroom is a mushroom that can be consumed, because it contains many nutrients such as vitamins, minerals, and amino acid. Nowadays, demand for oyster mushroom in Indonesia continues to increase, especially in the lowland like Tangerang. Knowing this, it needs effort to control the habitat that oyster mushrooms can be cultivated. This research was conducted by giving three treatments where the first treatment directly using sun light, the second treatment using a lamp with 5 watts power, and a third treatment using a lamp with 15 watts power. The data obtained are progress of baglog and temperature measurements in each treatment and then the data were analyzed using ANOVA test. With 5% significance level, research results between treatments using direct sunlight with the light from the lamp gives a significantly different effect, while between a lamp with 5 watt power and a lamp with 15 watt power do not give a significantly different effect. Best oyster mushroom growth obtained at treatment using a lamp with 5 watts power.